2000
DOI: 10.1017/s1041610200006578
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Effectiveness of Treatments for Depression in Elderly Medical Inpatients: A Systematic Review

Abstract: To determine the feasibility and effectiveness of treatments for depressed elderly medical inpatients, MEDLINE was searched for potentially relevant articles published from January 1987 to August 1997, using the keywords “depression or depressive disorder” (exploded) and “aged.” The bibliographies of relevant articles were searched for additional references. Fifteen reports met the following inclusion criteria: (a) published in English or French; (b) minimum age criterion of 55 and over or mean age 65 and over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 15 publications
0
9
0
3
Order By: Relevance
“…Unpublished studies were searched through a search of Dissertation Abstracts. Second, we examined the references of the six meta-analyses described above and four systematic reviews (Schneider and Olin, 1995;Cole et al, 2000;Arean and Cook, 2002;Blazer, 2003), which were identified in a systematic review of meta-analyses of psychological treatments for depression (Cuijpers and Dekker, 2005). And third, we examined the references of retrieved papers.…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
“…Unpublished studies were searched through a search of Dissertation Abstracts. Second, we examined the references of the six meta-analyses described above and four systematic reviews (Schneider and Olin, 1995;Cole et al, 2000;Arean and Cook, 2002;Blazer, 2003), which were identified in a systematic review of meta-analyses of psychological treatments for depression (Cuijpers and Dekker, 2005). And third, we examined the references of retrieved papers.…”
Section: Identification and Selection Of Studiesmentioning
confidence: 99%
“…Despite the apparent benefits of treatment, 11 up to 90% of cases of depression are not detected by attending physicians during the course of usual hospital care, 3,12 and few patients receive optimal treatment in hospital or after discharge. 12,13 Because a strategy of systematic detection and treatment has been shown to benefit elderly people with depression living in the community, [14][15][16][17][18] we conducted a randomized clinical trial to evaluate whether systematic detection and multidisciplinary treatment of depression could be effective in reducing symptoms of depression and improving mental and physical health status in elderly medical inpatients.…”
mentioning
confidence: 99%
“…While treating depression due to medical illness it is important to see that the antidepressants improve depression, and at the same time will not worsen medical condition or cause adverse effects [31]. To give an example, antidepressants with high anticholinergic property can worsen disease like diabetes mellitus, Alzheimer"s dementia, Parkinson"s disease and cardiovascular problems which are common in elderly [32]. It is equally important to minimise drug-drug interactions, especially given the number of medications elderly patients are often taking.…”
Section: Treatment:-mentioning
confidence: 99%